Xylella fastidiosa and Olive Quick Decline: Symptoms and Identification of an Insect Vectored Pathogen - Whitney C. Elmore; Jennifer L Gillett-Kaufman (EDIS)
A plant disease called Olive Quick Decline is killing olive trees throughout southern Italy. Although the pathogen that causes the disease is not known in Florida, it may spread to the state, which means that olive producers and homeowners with olives must watch for symptoms of the disease as well as for the leafhopper insects that spread it. This 3-page fact sheet written by Whitney Elmore and Jennifer L. Gillett-Kaufman and published by the Department of Entomology and Nematology explains how to monitor for the disease and its insect vectors and offers advice and assistance for commercial and hobby olive growers. http://edis.ifas.ufl.edu/in1165